Democracy and knowledge : innovation and learning in classical Athens - Ober, Josiah (Princeton University Press, 2008)
When does democracy work well, and why? Is democracy the best form of government? These questions are of supreme importance today as the United States seeks to promote its democratic values abroad. Democracy and Knowledge is the first book to look to ancient Athens to explain how and why directly democratic government by the people produces wealth, power, and security. Combining a history of Athens with contemporary theories of collective action and rational choice developed by economists and political scientists, Josiah Ober examines Athenian democracy's unique contribution to the ancient Gre.